The Australian Defence Force Mental Health Prevalence and Wellbeing Study: design and methods - Miranda Van Hooff; Alexander C. McFarlane; Christopher E. Davies; Amelia K. Searle; A. Kate Fairweather-Schmidt; Alan Verhagen; Helen Benassi; Stephanie E. Hodson (European Journal of Psychotraumatology, 2014)
Background: The Australian Defence Force (ADF) Mental Health Prevalence and Wellbeing Study (MHPWS) is the first study of mental disorder prevalence in an entire military population. Objective: The MHPWS aims to establish mental disorder prevalence, refine current ADF mental health screening methods, and identify specific occupational factors that influence mental health. This paper describes the design, sampling strategies, and methodology used in this study. Method: At Phase 1, approximately half of all regular Navy, Army, and Air Force personnel (n=24,481) completed self-report questionnaires. At Phase 2, a stratified sub-sample (n=1,798) completed a structured diagnostic interview to detect mental disorder. Based on data from non-responders, data were weighted to represent the entire ADF population (n=50,049). Results: One in five ADF members met criteria for a 12-month mental disorder (22%). The most common disorder category was anxiety disorders (14.8%), followed by affective (9.5%) and alcohol disorders (5.2%). At risk ADF sub-groups were Army personnel, and those in the lower ranks. Deployment status did not have an impact on mental disorder rates. Conclusion: This study has important implications for mental health service delivery for Australian and international military personnel as well as contemporary veterans.